Analisis Feminisme pada Lagu Bunda Ciptaan Melly Goeslow - Ela Nabila (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study looks at feminism in Melly Goeslow's song Bunda. This study aims to shed light on how popular music, in particular, shapes societal perceptions of women's roles. The research type is descriptive qualitative, and the methodology is qualitative. An analysis of feminism in Melly Goeslow's song Bunda serves as the study's data source. Melly Goeslow's song Bunda serves as the study's data source. Techniques for reading and taking notes were used in the data collection process. Finding significant patterns, comprehending phenomena, organizing, isolating, and arranging data, and drawing conclusions were all part of the data analysis process. According to the study's findings, there are four verses in Melly Goeslow's song Bunda that are analyzed for feminism. Marxist feminism, radical feminism, liberal feminism, and socialist feminism are the classifications for one verse, one verse, and one verse, respectively.